A pandemic is worldwide - Thomson, Sarah L. (Let's-read-and-find-out science., 2022)
This introduction to pandemics and their history shows readers how to stay safe, and also includes a glossary, an infographic on how the coronavirus spreads, a handwashing diagram and a timeline showing the pandemics of the past.